Mapping the Emotional Labour of Early Childhood Teachers in Indonesia: A Rasch Model Analysis - Melly Elvira; Syamsir Sainuddin; Akhmad Mukhlis (MASI Mandiri Edukasi, 2025)
This study addresses the limited empirical profiling of emotional labor among early childhood teachers in Indonesia by applying the Rasch Rating Scale Model. The research aims to examine teachers’ tendencies in emotional regulation, identify item difficulty levels, and map teacher ability distributions. A total of 312 early childhood teachers participated by completing an emotional labour scale representing four emotional-regulation dimensions. The reported logit range of −0.85 to 0.75 refers specifically to the distribution of item difficulty, which differs from the later reported teacher logit range (−3.5 to +3.2). The analysis revealed high measurement reliability (item reliability = 0.98; person reliability = 0.70) and satisfactory model fit indices. Teachers predominantly demonstrated reflective and authentic emotional regulation, as operationalised by lower difficulty on deep-acting and natural-expression items, indicating these strategies were more readily performed. These findings highlight that emotional labour among Indonesian early childhood teachers is grounded in empathy, warmth, and affective balance, forming an essential foundation for emotionally responsive and humanistic teaching practices.